Crystal structures of 5-amino-N-phenyl-3H-1,2,4-dithiazol-3-iminium chloride and 5-amino-N-(4-chlorophenyl)-3H-1,2,4-dithiazol-3-iminium chloride monohydrate - Yeo, C.I.; Tan, Y.S.; Tiekink, E.R.T. (International Union of Crystallography, 2015)
The crystal and molecular structures of the title salt, C8H8N3S2 +·Cl-, (I), and salt hydrate, C8H7ClN3S2 +·Cl-·H2O, (II), are described. The heterocyclic ring in (I) is statistically planar and forms a dihedral angle of 9.05(12)° with the pendant phenyl ring. The comparable angle in (II) is 15.60(12)°, indicating a greater twist in this cation. An evaluation of the bond lengths in the H2N - C - N - C - N sequence of each cation indicates significant delocalization of π-electron density over these atoms. The common feature of the crystal packing in (I) and (II) is the formation of charge-assisted amino-N - H⋯Cl- hydrogen bonds, leading to helical chains in (I) and zigzag chains in (II). In (I), these are linked by chains mediated by charge-assisted iminium-N+ - H⋯Cl- hydrogen bonds into a three-dimensional architecture. In (II), the chains are linked into a layer by charge-assisted water-O - H⋯Cl- and water-O - H⋯O(water) hydrogen bonds with charge-assisted iminium-N+ - H⋯O(water) hydrogen bonds providing the connections between the layers to generate the three-dimensional packing. In (II), the chloride anion and water molecules are resolved into two proximate sites with the major component being present with a site occupancy factor of 0.9327(18).